The Treatment of Distal Biceps Ruptures: An Overview - Cerciello, Simone; Visonà, Enrico; Corona, Katia; Ribeiro Filho, Paulo Roberto; Carbone, Stefano (Joints, 2018)
Traumatic lesions of the distal biceps brachii are uncommon. They often result from rapid elbow flexion against resistance. Conservative treatment is only indicated in low-demanding patient and in those who have severe comorbidities. Regarding the surgical approach, two options are available: the single- and the double-incision techniques. The former has been the first to be described and was associated with significant rate of neurologic complications. The second showed less frequent neurologic lesions, but considerable rate of heterotopic ossifications with reduced forearm movement. The choice of fixation device is another important issue. Cortical buttons, transosseous repair, suture anchors, and interference screws have shown satisfactory outcomes. However, cortical buttons have the best mechanical properties. Although a lack of high methodological quality studies emerges in the available literature, three recent systematic reviews and meta-analysis show interesting findings. Surgical reinsertion of the distal biceps brachii yields satisfactory clinical outcomes both with the single- and double-incision techniques. Higher prevalence of nerve injuries is associated with the single-incision techniques, whereas higher prevalence of heterotopic ossification is reported with double-incision techniques. Thus far, there is no sufficient evidence to support one option and the choice is mainly based on surgeon's experience.
Keywords: distal biceps; rupture; double-incision technique; heterotopic ossification